Study on the Effect and Mechanism of Aerodynamic Measures for the Vortex-Induced Vibration of Separate Pairs of Box Girders in Cable-Stayed Bridges - Han Xin He; Jia Wu Li (Shock and Vibration)
Although not always resulting in catastrophic failures, vortex-induced vibration (VIV) response can seriously impact the fatigue life and functionality of bridges, especially for separate pairs of box girders in cable-stayed bridges. This study investigates the effects of three aerodynamic measures: grating, inclined web plate, and the baffles on separated box girders in the cable-stayed bridges. The experimental result indicates that the grating of different opening ratios can control the vortex-induced vibration effectively, and the optimized grating opening ratio set in this paper is 40%. Increasing the angle of inclined web plate has a great control on mitigation of the vortex-induced vibration. However, there is an optimum angle where the amplitude of vortex-induced vibration is the smallest at low wind speed. The amplitude of vortex-induced vibration becomes larger with the increase of the web inclined angle that exceeds the optimum angle. Comparatively, the baffles installed on both sides of the inclined webs are more effective to restrain the vortex-induced resonance. The Computational Fluent Dynamics (CFD) software is utilized to investigate the mechanism of the experimental results.